2015
DOI: 10.1093/ejcts/ezv336
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative anxiety and depression after surgical treatment for lung cancer

Abstract: Postoperative psychological distress and, in particular, depression increased after surgical treatment for lung cancer. Postoperative anxiety and depression were aggravated by residual symptoms after surgery. Careful psychological evaluation and appropriate management are required to improve patients' quality of life after lung cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 22 publications
4
72
1
1
Order By: Relevance
“…Park et al conducted their study among 278 patients undergoing curative surgical resection for primary lung cancer. They reported that severe pain was identified as a risk factor for postoperative depression after adjusting for preoperative depression (OR=3.9; P=0.001) (22). The assessment of nutritional status in patients with metastatic NSCLC stage IV or extended stage SCLC referred for chemotherapy, which was performed by Giannousi et al, revealed significant correlations between the MNA score and depression (r=0.275; P=0.002) while the correlation between the MNA score and anxiety was insignificant (23).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al conducted their study among 278 patients undergoing curative surgical resection for primary lung cancer. They reported that severe pain was identified as a risk factor for postoperative depression after adjusting for preoperative depression (OR=3.9; P=0.001) (22). The assessment of nutritional status in patients with metastatic NSCLC stage IV or extended stage SCLC referred for chemotherapy, which was performed by Giannousi et al, revealed significant correlations between the MNA score and depression (r=0.275; P=0.002) while the correlation between the MNA score and anxiety was insignificant (23).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates for fatigue (42.2%) and anxiety (20.9%) were similar to those observed in previous studies involving lung cancer survivors (16.8% to 57% and 19.75 to 34%, respectively) . The prevalence rate for depression (38.9%) was somewhat higher relative to those reported in previously published research (8.9% to 33%) . In addition, previous studies have reported various prevalence rates for fatigue, anxiety, and depression in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The result is consistent with a recent report and depression after operation may be related to residual symptoms including pain and dyspnea. [29] However, lung cancer patients receiving operation were mostly in earlier stages and were expected live longer to receive psychiatric interventions. On the contrary, patients with brain metastasis, or those receiving CT, RT, and EGFR-TKI treatments were in late stages.…”
Section: Discussionmentioning
confidence: 99%